(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2025)
Soil salinization is one of the most common land degradation processes, especially in arid and semi-arid regions, where precipitation exceeds evaporation, Under such climatic conditions, soluble salts are accumulated in the soil, influencing soil properties with ultimate decline in productivity. Therefore, the mapping of soil degradation by salinity has a key role in understanding the Spatial variation, rate and direction of degradation. The research provides a model for monitoring and mapping saline soil and its changes between time and time in a Moza wadi basin distributed using remote sensing technology, By tracking the salinity of the soil and its changes using all the spectral indicators, the results of the research found that the soil in the basin is subject to deterioration salinity between time and time, This is confirmed by the decline in the area of the area which is characterized as non-saline by 120.1 km2, The area of the saline area was 41.8 km2, the area of the saline area increased by about 29 km2, and the area of the soils with high salinity About 49.2 km2 of the total area of the basin.